Media Pembelajaran Berbasis Visual Berbentuk Permainan Tradisional (Cublak-cublak Suweng) untuk Meningkatkan Kualitas Belajar Mengajar di MI/SD - Alisia Zahro’Atul Baroroh (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Learning media are tools that assist in teaching and learning activities, helping teachers represent concepts that cannot be conveyed through words or sentences alone. Through a playful approach, this article proposes visual-based learning media in the form of a traditional game (cublak-cublak suweng) in an engaging and enjoyable manner for students. The article discusses the benefits of the traditional game (cublak-cublak suweng) as a learning resource. By combining conventional learning with elements of play, this method is expected to increase students' interest in learning media and deepen their understanding of fundamental scientific concepts. The research method used in this study is descriptive qualitative. The methodology aims to gain a deeper understanding of visual-based learning media in the form of the traditional game (cublak-cublak suweng). In this study, the researcher used several data collection techniques, including observation, interviews, and documentation.